Teaching Federalism Multidimensional Approaches - Kincaid, John; Leckrone, J. Wesley (Elgar Guides to Teaching, 2023)
Teaching Federalism presents innovative ideas for teaching a wide variety of key concepts of federalism and federal-country cases. Each chapter introduces a topic, explains its place in federalism research, and provides learning objectives, pedagogical tools, and questions for class discussions, student essays, and examinations. Evaluation and reading suggestions are included as well. The book covers twenty substantive facets of federalism important for understanding contemporary issues of federalism and federation, such as power distribution, second chambers, high courts, intergovernmental relations, fiscal federalism, multinational federalism, conflict resolution, indigenous peoples, gendered federalism, and secession. Also included are case-study examples for teaching about federalism in Germany, India, Nigeria, Switzerland, and the United States. Educators around the world who teach federalism or wish to do so will find this a wonderful resource for lesson plans on a wide variety of issues related to federalism. Students studying federalism will also find it invaluable as an introductory resource for important topics and readings on the subject.